3H-Pyrroles as a platform for the catalyst-free construction of dihydropyrrolo[2, 1-b]oxazoles: [4 + 2]-cycloaddition vs [2 + 3]-annulation with 1-cyano-3-hydroxyalkynes. Issue 4 (24th January 2019) - Oparina, Ludmila A.; Shabalin, Dmitrii A.; Kolyvanov, Nikita A.; Ushakov, Igor' A.; Mal'kina, Anastasiya G.; Vashchenko, Alexander V.; Trofimov, Boris A.
Graphical abstract: Highlights: An efficient, catalyst-free approach to pyrrolooxazoles. The 2-(dihydropyrrolo[2, 1- b ]oxazolylidene)acetonitriles were obtained in good yields. Available starting materials are used. The [2 + 3]-annulation of 3H-pyrroles with cyano-3-hydroxyalkynes. Structural elucidation using NMR and single crystal X-ray studies. Abstract: Non-aromatic pyrrole isomers, 3, 3-dialkyl-2-aryl-3 H -pyrroles, were reacted with 1-cyano-3-hydroxyalkynes under mild, catalyst-free conditions (20–60 °C) to regio- and stereoselectively afford ( Z )-2-(dihydropyrrolo[2, 1- b ]oxazolylidene)acetonitriles in 62–82% yield, thus evidencing the preference for [2 + 3]-annulation over the [4 + 2]-Diels-Alder alternative. The reaction involves initial nucleophilic addition of the pyrrole moiety at the triple bond followed by tandem ring closure of an anionic intermediate.